2014
DOI: 10.3390/md12053072
|View full text |Cite
|
Sign up to set email alerts
|

Cracking the Cytotoxicity Code: Apoptotic Induction of 10-Acetylirciformonin B is Mediated through ROS Generation and Mitochondrial Dysfunction

Abstract: A marine furanoterpenoid derivative, 10-acetylirciformonin B (10AB), was found to inhibit the proliferation of leukemia, hepatoma, and colon cancer cell lines, with selective and significant potency against leukemia cells. It induced DNA damage and apoptosis in leukemia HL 60 cells. To fully understand the mechanism behind the 10AB apoptotic induction against HL 60 cells, we extended our previous findings and further explored the precise molecular targets of 10AB. We found that the use of 10AB increased apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 50 publications
(77 reference statements)
0
35
0
Order By: Relevance
“…In our previous report, 10-acetylirciformonin B, a marine sesterterpenoid analog, significantly inhibited Topo IIα activity35. Such findings encouraged us to evaluate the effect of the isolates on Topo II activity.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…In our previous report, 10-acetylirciformonin B, a marine sesterterpenoid analog, significantly inhibited Topo IIα activity35. Such findings encouraged us to evaluate the effect of the isolates on Topo II activity.…”
Section: Resultsmentioning
confidence: 74%
“…The assay was performed as described previously3538. Standard relaxation reaction mixtures (20 μL) containing 50 mM Tris–HCl (pH 8.0), 10 mM MgCl 2 , 200 mM potassium glutamate, 10 mM dithiothreitol, 50 μg/mL bovine serum albumin, 1 mM ATP, 0.3 μg of pHOT1 plasmid DNA, two units of human topoisomerase II (Topogen, Columbus, OH, USA), and the indicated concentrations of etoposide and the compounds were incubated at 37 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, oxidative stress‐generating drugs may induce apoptosis . Accordingly, we found that CHW09 induced ROS and apoptosis of Ca9‐22 oral cancer cells in terms of detection of annexin V and cleavage of PARP and cleavage of caspases 3/8/9, suggesting that both intrinsic and extrinsic apoptosis signaling were involved in CHW09‐induced apoptosis.…”
Section: Discussionmentioning
confidence: 83%
“…A ROS reacting agent 2′,7′‐dichlorodihydrofluorescein diacetate (H 2 DCF‐DA) (Sigma‐Aldrich; St. Louis, MO) can react with ROS and become a fluorescent molecule for flow cytometry analysis, as previously described . After drug treatment, cells were treated with 100 nM of H 2 DCF‐DA in PBS for 30 min in an incubator.…”
Section: Methodsmentioning
confidence: 99%
“…Mounting evidence demonstrated that ROS generation and mitochondrial membrane depolarization may lead to DNA damage [33,34,35,36,37,38] and apoptosis [38,39,40,41] in drug-treated cancer cells. Accordingly, TFB also showed a correlation between oxidative stress and DNA damage in its antiproliferative and apoptotic effects of two oral cancer cells (Ca9-22 and CAL 27) in our study.…”
Section: Discussionmentioning
confidence: 99%